PENGARUH IMPLEMENTASI INTERNAL SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA OPERASIONAL PERUSAHAAN (STUDI KASUS PADA PT. PAN BROTHERS TBK, BOYOLALI) - Sugiharto, Dian Aulia; Supaya, Sandi -; Nurkhayati, Isnaini - (Admisi dan Bisnis, 2016)
This study aimed to know the influence of theimplementation of internal supply chainmanagement on company's operationalperformance at PT. Pan Brothers Tbk &Groups, Boyolali. The method used to collectthe data is questionnaire. The samplingmethods used are the purposive andincidental sampling with 50 respondents from100 population. The analysis methods usedare the validation test, reliability test, simplelinear regression, T test, and determinationcoefficient with SPSS 20. The empirical resultshowed that there is a positive and significantinfluence of the information sharing oncompany's operational performance. So, itcan be concluded that the implementation ofsupply chain management (informationsharing) affect significantly towardcompany's operational performance with thedetermination coefficient of R square 65.7%,while 34.3% is explained by other variables(e.g. long term relationship, cooperation,integration process).